Cobalt Catalysis: C7 Alkynylation of Indolines with a Bromoalkyne - Manisha, Manisha; Gupta, Shiv Shankar; Sharma, Upendra (Synthesis, 2024)
A method for the cobalt-catalyzed C-7 alkynylation of indolines with (bromoethynyl)triisopropylsilane under mild conditions is described, leading to a diverse range of alkynylated indolines in good to excellent yields. Kinetic isotope studies indicate that the formation of a cobaltacycle might be the turnover-limiting step. Additionally, a gram-scale synthesis and oxidation of an indoline to an indole have been carried out successfully with excellent yields.
Keywords: cobalt; indolines; bromoalkyne; C–H activation; alkynylation